Aktivitas Antihiperurisemia Ekstrak Etanol Daun Sungkai (Peronema canescens Jack) Pada Mencit Putih Jantan - Madyawati Latief; Indra Lasmana Tarigan; Putri Maya Sari; Fiolita Etsa Aurora (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Hyperuricemia is a disease caused by an increase in uric acid levels in the blood. Currently, various treatments are developed by utilizing natural ingredients as an anti-hyperuricemia. Sungkai (Peronema canescens Jack) is one of the plants that contain a natural compound that can use as an anti-hyperuricemia treatment is the leaves of sungkai (Peronema canescens Jack.). The aim of this study to determine the anti-hyperuricemia activity of the ethanol extract of Sungkai leaves. The test animals used in this study were male white mice Wistar strain. This study used a completely randomized design (CRD) with 5 groups consisting of negative control (Na CMC 0.5%) positive control (allopurinol 10 mg / kg BW), treatment 1 (extract 125 mg / kg BW), treatment 2 (extract 250 mg / kg BW) and treatment 3 (extract 500 mg / kg BW). The parameters seen were uric acid levels measured using the POCT (Point of Care Test) method and analyzed using One Way Anova statistical analysis and Duncan's continued test. Our results showed that the treatment group with a dose of 125-500 mg / Kg BW reduce uric acid levels in mice. The best dose was a dose of 500 mg / Kg BW in reducing uric acid levels in mice with percent decline of 38.66%.